2011
DOI: 10.1021/jz200117r
|View full text |Cite
|
Sign up to set email alerts
|

On the Unusual Properties of Anatase TiO2 Exposed by Highly Reactive Facets

Abstract: As an important metal oxide, anatase titanium dioxide has been widely investigated because of its many promising properties. The properties of anatase TiO2 crystals are largely determined by exposed external surfaces. Since the breakthrough in synthesizing anatase TiO2 single crystals with a large percentage of highly reactive {001} facets in 2008, many unusual properties and applications of these {001} facets dominant in anatase TiO2 have been explored theoretically and experimentally, showing the industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(160 citation statements)
references
References 60 publications
2
158
0
Order By: Relevance
“…Previous studies have shown that anatase is active in both catalysis and photocatalysis, and is the most used polymorph of TiO 2 . 15,46,51,52 Although several factors such as facets and surface areas have been considered to contribute to the high activity of anatase, 53 the type and activity of surface OH groups might also play a critical role. The present work demonstrated that the crystal phase of TiO 2 determines the nature of the surface OH groups, which then determines the reaction of NO 2 on TiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that anatase is active in both catalysis and photocatalysis, and is the most used polymorph of TiO 2 . 15,46,51,52 Although several factors such as facets and surface areas have been considered to contribute to the high activity of anatase, 53 the type and activity of surface OH groups might also play a critical role. The present work demonstrated that the crystal phase of TiO 2 determines the nature of the surface OH groups, which then determines the reaction of NO 2 on TiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that an excess of light promotes a faster electron-hole recombination and the low activation energy of photocatalytic reactions (5-20 kJ/mol), compared with ordinary thermal reactions. In slurry type systems, catalyst loading is an important design parameter for the effective use of reactor space and photocatalyst and a wide range (0.15 to 8 g/L) of optimal catalyst loading in aqueous suspensions has been reported for different photocatalyst systems and reactor configurations [1,12,[91][92][93][94][95][96][97][98][99], Figure 7: Figure 7. Schematic diagram of Channelled Optical Fiber Reactor (COFR) system for gas-phase photocatalytic degradation of volatile organic compounds [1].…”
Section: Photocatalytic Reactor Designmentioning
confidence: 99%
“…Since reported by Yang et al [8], many research have concentrated on the fabricating of TiO 2 sheets exposed high percentage of {0 0 1} facets and exploring these sheets for the photocatalytic degradation of pollutants, hydrogen production, etc. [9][10][11][12][13][14][15][16][17]. In these researches, anatase TiO 2 crystals exposing a high percentage of {0 0 1} facets were synthesized using a capping agent or a co-capping agent containing HF.…”
Section: Introductionmentioning
confidence: 99%